TRANSFORMASI ANALISIS KEBIJAKAN, MODEL, TAHAPAN, DAN IMPLEMENTASINYA DALAM PENGELOLAAN PENDIDIKAN MODERN - Hafiz Hidayat; Elmasi Tri Oktaviani; Salsabila; Dutika Handayani; Fenri Naldi; Emi Sofia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Policy analysis has become an essential component in improving educational governance, ensuring that decisions are evidence-based, systematic, and aligned with societal needs. This article reviews various policy analysis models, their operational stages, and their practical implications in modern education management. Findings reveal that rational, incremental, and mixed scanning models provide distinct advantages depending on context, while the stages of policy analysis problem identification, formulation, implementation, and evaluation play a crucial role in guiding decision makers. The article concludes with recommendations for strengthening analytical capacity, integrating data-driven decision-making, and enhancing collaboration across stakeholders.